Development of composing skills in Filipino among second graders through directed reading lessons - Reyes, Jo Anne S. (Education Quarterly, 2013)
The study investigated the development of composing skills in Filipino among second graders through Directed Reading Lessons (DRLs). The guiding questions were: (1) Do the Directed Reading Lessons (DRLs) improve the composing skills in Filipino among Grade 2 children? (2) In what ways did the children's composing skills improve?